The gentleman's gambit - Dunmore, Evie (Dunmore, Evie. League of extraordinary women series, 2023)
"Bookish suffragist Catriona Campbell is busy: An ailing estate, academic writer's block, and a tense time for England's women's rights campaign--the last thing she needs is to be stuck playing host to her father's distractingly attractive young colleague. Deeply introverted Catriona lives for her work at Oxford and her fight for women's suffrage. She dreams of romance, too, but since all her attempts at love have ended badly, she now keeps her desires firmly locked inside her head--until she climbs out of a Scottish loch after a good swim and finds herself rather exposed to her new colleague. Elias Khoury has wheedled his way into Professor Campbell's circle under false pretenses: He did not come to Oxford to classify ancient artifacts; he is determined to take them back to his homeland in the Middle East. Winning Catriona's favor could be the key to his success. Unfortunately, seducing the coolly intense lady scholar quickly becomes a mission in itself and his well-laid plans are in danger of derailing.... Forced into close proximity in Oxford's hallowed halls, two very different people have to face the fact that they might just be a perfect match. Soon, a risky new game begins that asks Catriona one more time to put her heart and wildest dreams at stake"--